Critical Success Factors Evaluation for Blockchain’s Adoption and Implementing - Mohamed O. Grida; Samah Abd Elrahman; Khalid A. Eldrandaly (Systems, 2022)
Blockchain has completely changed how business is performed today, thus making it one of the most disruptive technologies in recent times. However, it is a challenging task to adopt and implement blockchain technologies in different services and industries. Therefore, this study introduces a framework for investigating critical factors influencing the successful adoption of blockchain technologies in different applications and prioritizes them using the hierarchical Decision-Making Trial and Evaluation Laboratory (DEMATEL) technique. First, it provides fourteen critical success factors with the help of the extant literature and further classifies them into three categories: technological, organizational, and environmental. In addition, a set of sixteen key performance indicators (KPI) of successful blockchain adoption is introduced and classified into five categories: overall performance, system robustness, data robustness, accessibility, and overall cost. Then, the fourteen success factors are ranked based on their degree of prominence and relationships. It is concluded that environmental factors are the most critical factors for successful blockchain adoption, and law and policies and competitive pressure are the top two factors needed for blockchain adoption. In the technological context, only blockchain scalability is ranked among the top significant factors for blockchain adoption. On the other hand, adequate resources, top management support, and financial constraints are highly ranked in the organizational context.